1984
DOI: 10.1007/bf01318522
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic granulomatosis and sarcoidosis

Abstract: The etiology of hepatic granulomatosis discovered in patients with normal chest roentgenograms is controversial. Among 18 such patients studied in recent years, sarcoidosis was identified as the cause in 15 by demonstration of granulomatous inflammation in extrahepatic tissues, employing a variety of biopsy methods. Serum angiotensin levels were raised in all 10 patients tested and gallium scans were helpful in four of six cases. Prolonged fever was the most common symptom, but three patients had severe right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Severe pain in the right upper quadrant can be present even without biliary injury. 12,14,15,23 Diagnosis of hepatic granulomatosis A comprehensive medical history and physical examination should be pursued along with an extensive medication and travel history. A reasonable initial approach is to search first for the most common causes of granulomatous liver disease in a particular population to avoid unnecessary testing.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Severe pain in the right upper quadrant can be present even without biliary injury. 12,14,15,23 Diagnosis of hepatic granulomatosis A comprehensive medical history and physical examination should be pursued along with an extensive medication and travel history. A reasonable initial approach is to search first for the most common causes of granulomatous liver disease in a particular population to avoid unnecessary testing.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Fox et al 57 reported negative Kveim-Siltzbach responses in 9 tested patients with PBC-associated hepatic granulomas on liver biopsy. This finding would argue against coexistent sarcoidosis 60 however, report that negative Kveim-Siltzbach reactions are also a common occurrence in hepatic sarcoidosis and cannot serve as an indication of its absence. Furthermore, 2 cases with concurrent positive Kveim-Siltzbach reactions and elevated AMA titers suggestive of coexistent sarcoidosis and PBC, respectively, have been noted in the literature and are listed in Table 1.…”
Section: Pbc and Sarcoidosis: Distinct Entities Or "Overlap Syndrome"mentioning
confidence: 59%
“…There are a few reports of a variety of treatments for liver involvement with sarcoid. These include chloroquine (10), chlorambucil (11), methotrexate (12), and D-penicillamine (5). Drugs used are also based on the similarity at times between sarcoid of the liver and primary biliary cirrhosis (PBC).…”
Section: Discussionmentioning
confidence: 99%